2005
DOI: 10.12702/1984-7033.v05n01a14
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and path analysis in peanut

Abstract: -Genetic parameters of agronomical traits of peanut were estimated and the coefficients of genotypic correlation between the grain yield and the primary components of the yield apportioned into direct and indirect effects. The cultivars (Tatu, BR 1, L.7 Vermelha, CNPA 75 AM, CNPA 76 AM, CNPA 68 AM, L.8.14.12, L.8.14.01 and L.7 Bege)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 6 publications
5
20
0
1
Order By: Relevance
“…These results are in accordance with the reports of Abraham (1990), Moinuddin (1997), Gomes et al, (2005), Kalmeshwar et al, (2006), Praveen Kumar (2006) and Kumar et al, (2012) in groundnut.…”
Section: Resultssupporting
confidence: 92%
“…These results are in accordance with the reports of Abraham (1990), Moinuddin (1997), Gomes et al, (2005), Kalmeshwar et al, (2006), Praveen Kumar (2006) and Kumar et al, (2012) in groundnut.…”
Section: Resultssupporting
confidence: 92%
“…For a better understanding of the factors involved in the associations of traits, Wright (1921) (Gonçalves et al 2003, Gomes and Lopes 2005, Bárbaro et al 2006. Path analysis can therefore be made from genetic or environmental correlations (Cruz 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of correlations can be more clearly understood in the path analysis, which allows the partitioning of correlation in direct and indirect effects and is therefore a valuable tool in breeding programs of various crops (Gomes and Lopes 2005, Gomes et al 2007, Vieira et al 2007). In literature, several studies have demonstrated the utility of correlation analysis in peanut selection based on plant and reproductive traits (Lakshmaiah et al 1983, Santos et al 2000, Gomes and Lopes 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, several studies have demonstrated the utility of correlation analysis in peanut selection based on plant and reproductive traits (Lakshmaiah et al 1983, Santos et al 2000, Gomes and Lopes 2005.…”
Section: Introductionmentioning
confidence: 99%